INTERANNUAL VARIABILITY OF SEA LEVEL ANOMALY (SLA) IN THE WESTERN SUMATRA COASTAL WATERS DRIVEN BY ENSO AND IOD MODULATIONS - Azuga, Nabila Afifah; Habibullah, Ahmad Dhuha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This study aims to investigate the interannual variability of Sea Level Anomaly (SLA) along the western coast of Sumatra waters, focusing on the influences of the El Niño-Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) in modulating SLA patterns. Using 31 years (1993-2023) of a gridded dataset from Copernicus Marine Service (CMS) and climate indices as the reference, the interplay between SLA and climate modes (ENSO and IOD) was determined through lag/lead correlation and spatial distribution analysis. The analysis shows a clear inversive relationship between ENSO and SLA, with a one-month delayed negative correlation (r= -0.41), indicating that SLA increases during the La Niña phase due to shifting in atmospheric and oceanic conditions. Similarly, SLA exhibits a negative correlation with DMI (r= -0.46) without any lag, suggesting a rapid response of SLA to IOD. Spatial analysis further demonstrates that ENSO and IOD most strongly influence SLA along Sumatra’s coast within the first 1–3 months. These findings reveal that ENSO and IOD modulate SLA variability with distinct spatiotemporal characteristics, providing crucial insights for understanding coastal dynamics and enhancing mitigation strategy for sea level-related disasters in the western coastal region of Sumatra